TINJAUAN YURIDIS TERHADAP PENYALAHGUNAAN VISA KUNJUNGAN OLEH WARGA NEGARA ASING DI INDONESIA - Ulan Yuktatma, Ni Nyoman; Yusa Darmadi, Anak Agung Ngurah (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 03, Mei 2014, 2014)
A visa is a document issued by a State in order to give permission to someone to enter its territory, within a particular period and purpose. Visa is divided into several types, depends on its functions. However, in practice in Indonesia, it is often found cases regarding the misuse of visa by foreigners, as they use it to live and work in Indonesia. This paper will discuss the violation of visa visit by foreign nationals in Indonesia. This paper will also discuss the Indonesian government's efforts to solve this legal issue.
Keywords: Visa visit, Abuse, Prevention